2016
DOI: 10.1515/biol-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of miR-132 in CRC tissues and its inhibitory function on tumor progression

Abstract: Objectives Colorectal cancer (CRC) is among the most common types of malignancies in the worldwide, and microRNAs (miRNAs) emerge as key regulators in carcinogenesis and tumor progression. Here we intended to address the expression and function of miR-132 in CRC cells. Methods Paired CRC tissues and several established cell lines were firstly collected. We performed qPCR to detect the expression of miR-132 in these tissues and cell lines. Cell proliferation and apoptosis were respectively monitored by CCK-8 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Cancer has been associated with a global defect in miRNA production, possibly due to genetic or epigenetic changes affecting the miRNA genes, or because of alterations in some components of the miRNA biogenesis pathway such as Drosha or Dicer [ 5 , 37 ]. Moreover, matching the results shown in this study, hsa-miR-143-3p has previously been reported to be downregulated in tumor samples with respect to marginal normal mucosa of CRC patients [ 38 ], and hsa-miR-132-3p levels were found to be lower in CRC cell lines with respect to normal colonic cells, as well as in CRC tumor samples when compared to their paired normal tissue [ 18 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Cancer has been associated with a global defect in miRNA production, possibly due to genetic or epigenetic changes affecting the miRNA genes, or because of alterations in some components of the miRNA biogenesis pathway such as Drosha or Dicer [ 5 , 37 ]. Moreover, matching the results shown in this study, hsa-miR-143-3p has previously been reported to be downregulated in tumor samples with respect to marginal normal mucosa of CRC patients [ 38 ], and hsa-miR-132-3p levels were found to be lower in CRC cell lines with respect to normal colonic cells, as well as in CRC tumor samples when compared to their paired normal tissue [ 18 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%